2016
DOI: 10.1597/14-270
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Tongue Blade Length of the Dingman Mouth Gag for Japanese Pediatric Patients with Cleft Palate and Mandibular Micrognathia

Abstract: Objective Our objective is to determine appropriate specifications for smaller tongue blade for Japanese pediatric patients with cleft palate (CP) and mandibular micrognathia. Patients We investigated 59 patients who underwent palatoplasty. Patients were divided into two groups: the micrognathia (MG) group consisted of 11 patients and the normognathia (NG) group consisted of 48 patients. Interventions The following five items were investigated retrospectively: (1) gender, (2) cleft type, (3) age at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…So in the previous study, we attempted to determine appropriate tongue blade length for Japanese pediatric patients with CP and mandibular micrognathia and concluded that it was difficult to predict the distance from the tongue blade base to the posterior pharyngeal wall (Dis) on the basis of the patient's age or weight at the time of surgery, which could be measured preoperatively, and as the minimum Dis value in the MG group was 55 mm, preparing a tongue blade of approximately 50 mm in length, which is shorter than the current minimum specifications, might be appropriate when fitting a Dingman Mouth Gag for Japanese pediatric patients with CP and mandibular micrognathia [1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So in the previous study, we attempted to determine appropriate tongue blade length for Japanese pediatric patients with CP and mandibular micrognathia and concluded that it was difficult to predict the distance from the tongue blade base to the posterior pharyngeal wall (Dis) on the basis of the patient's age or weight at the time of surgery, which could be measured preoperatively, and as the minimum Dis value in the MG group was 55 mm, preparing a tongue blade of approximately 50 mm in length, which is shorter than the current minimum specifications, might be appropriate when fitting a Dingman Mouth Gag for Japanese pediatric patients with CP and mandibular micrognathia [1].…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study, we assessed the appropriate tongue blade length of the Dingman Mouth Gag for Japanese CP patients with mandibular micrognathia, it was suggested that a tongue blade of approximately 50 mm in length, shorter than the current minimum specifications might be appropriate [1].…”
Section: Introductionmentioning
confidence: 99%